2006
DOI: 10.1093/aje/kwj309
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Risk of Postmenopausal Breast Cancer in a 20-year Follow-up

Abstract: Dietary fat in midlife has not been associated with breast cancer risk in most studies, but few have followed women beyond one decade. The authors examined the relation of dietary fat, assessed by repeated questionnaires, to incidence of postmenopausal breast cancer in a cohort of 80,375 US women (3,537 new cases) prospectively followed for 20 years between 1980 and 2000. The multivariable relative risk for an increment of 5% of energy from total dietary fat intake was 0.98 (95% confidence interval: 0.95, 1.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
69
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 34 publications
6
69
2
2
Order By: Relevance
“…The lack of associations with total fat, MUFA, PUFA or SFA is in agreement with many earlier cohort studies (e.g. Kim et al, 2006). However, statistically significant positive associations were recently found for total fat both in a meta-analysis (Boyd et al, 2003) and a cohort study (Thiebaut et al, 2007); also for MUFA, PUFA (Thiebaut et al, 2007) and for SFA in both these studies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The lack of associations with total fat, MUFA, PUFA or SFA is in agreement with many earlier cohort studies (e.g. Kim et al, 2006). However, statistically significant positive associations were recently found for total fat both in a meta-analysis (Boyd et al, 2003) and a cohort study (Thiebaut et al, 2007); also for MUFA, PUFA (Thiebaut et al, 2007) and for SFA in both these studies.…”
Section: Discussionsupporting
confidence: 92%
“…The protective effect of MUFA in older women support is consistent with the Swedish mammography cohort on postmenopausal women (Wolk et al, 1998) but not with a nested casecontrol (Wirfalt et al, 2002) and several cohort studies, which, with some exceptions (Holmes et al, 1999;Voorrips et al, 2002), have reported no or even a positive association with MUFA (Velie et al, 2000;Smith-Warner et al, 2001;Boyd et al, 2003;Cho et al, 2003;Kim et al, 2006;Thiebaut et al, 2007). We also found a protective effect of PUFA in older women, as in a few case -control studies (Boyd et al, 2003) but not with any earlier prospective cohorts (Boyd et al, 2003;Kim et al, 2006;Thiebaut et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations